Pengembangan Media Pembelajaran Logika Boolean Berbasis Web Menggunakan Pyodide Dengan Pendekatan Prototyping Bagi Mahasiswa Teknik Informatika - Alfian, Zurnan; Effendi, Andre; Priyogi, Fairus; Yatim, Rajwaa Nazir (Journal of Informatics Management and Information Technology, 2026)
Boolean logic learning is a fundamental competency that must be mastered by Informatics Engineering students as a foundation for understanding digital computation and programming concepts. However, the presentation of theoretical materials often makes it difficult for students to visualize the relationship between binary inputs and logical operation outputs, which leads to a low level of conceptual understanding. This study aims to develop a web-based Boolean logic learning medium that integrates the Pyodide engine to provide interactive simulations directly within a browser environment. The application is designed to assist students in understanding Boolean logic operations through truth table visualization, binary input simulations, and mini-game features as learning exercises. The research method employs a prototyping approach consisting of needs analysis, system design, application implementation, and user evaluation stages. The evaluation was conducted through pilot testing involving five Informatics Engineering students from Universitas Pamulang to assess the application’s functionality, usability, and initial user acceptance as a learning medium. The results indicate that the application produces outputs that are consistent with Boolean logic truth tables and achieves a high level of user acceptance. These findings suggest that the developed learning medium has the potential to serve as an effective interactive learning tool in supporting students’ initial understanding of Boolean logic concepts prior to broader-scale testing.